Erratum to: Search for diboson resonances in hadronic final states in 139 fb−1 of pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; et al. (Journal of high energy physics, 2020)
A mistake was identified for the paper [1] in the treatment of the radion [2] cross-sections, which resulted in multiple changes.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol, -1 in fb-1 ist hochgestellt
The ATLAS collaboration: G. Aad, C.F. Anders, V. Andrei, C. Antel, A.C. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, L. Helary, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 11.03.2021